Sample-level PRRSV RT-PCR prevalence in pigs in mainland China (2004–2025): A systematic review and meta-analysis - Mengke Si; Yiwei Wang; Xiang Li; Junxue Qiu; Xiaoyu Chong; Baolei Yang; Mingfeng Chu; Yuchen Liang; Wei Cheng; Jingyan Zhang; Xuelong Chen; Yanping Qi (Preventive Veterinary Medicine, 2026)

Integrative transcriptomics and metabolomics analyses reveal changes in meat quality and muscle lipid metabolism in sheep supplemented with rumen-protected glucose - Yanping Liang; Jianchuan Shi; Xindong Cheng; Mengyu Feng; Dan Jiao; Xia Du; Kaixi Ji; Shoubin Hu; Qiaoxia Dong; Guo Yang (Meat Science, 2026)

Influence of organosilicon spray adjuvants on the growth of maize and wheat: a comparison with exogenous silica fertilizer under drought conditions - Yanping Feng; Yuanqiang Luo; Yu Xiang; Mengting Liang; Yuanyuqing Xiao; Yuping Zhang (Cereal Research Communications, 2026)

Non-invasive Computational Techniques for Diagnosing Myocardial Ischemia: Challenges and Future of FFRCT/iFRCT - Bao Li; Jincheng Liu; Yang Yang; Hao Sun; Chi Zhu; Leo Hwa Liang; Zijie Wang; Luyao Fan; Suqin Huang; Xueke Li; Guangfei Li; Liyuan Zhang; et al. (Annals of Biomedical Engineering, 2026)

Water temperature affects pathogenicity of ranavirus to adult bullfrogs - Yanping Ma; Le Hao; Xi Liang; Gang Wang; Zhenxing Liu (Aquaculture, 2026)

High pH decreases the contents of stable organic nitrogen fractions and nitrogen supply capacity by inhibiting soil organic carbon in saline-sodic paddy fields - Baishun Liu; Lihua Huang; Fengyi Zhang; Jinghui Cai; Lei Tian; Xiaotong Jiang; Yanping Liang; Ge Zhu; Guangzhi Huang (Soil and Tillage Research, 2026)

A simplified RUBY reporter-enabled hairy-root system for rapid evaluation of genome editing and gene function in grapevine - Chong Ren; Yanping Lin; Mohamed Salaheldin Mokhtar Mohamed; Chencong Liu; Zhenchang Liang (Planta, 2026)

Non-Invasive functional assessment of severity in cerebral arterial stenosis using cerebral flow fraction: A hemodynamic study - Hao Sun; Bao Li; Zijie Wang; Liyuan Zhang; Jun Zhao; Yanping Zhang; Guangfei Li; Jinli Ding; Yanjun Gong; Hwa Liang Leo; Youjun Liu (Medical & Biological Engineering & Computing, 2026)

Identification and validating native biocontrol bacteria Bacillus strain MZ3-12 against bacterial wilt - Xiao Zhou; Yue Qing; Yanping Wang; Haibin Deng; Jun Wang; Mi Kuang; Xuefeng Luo; Chenran Zhao; Zheng Sun; Ye Wang; Liang Yang; Wei Ding (Pesticide Biochemistry and Physiology, 2026)

GhDREB1B-GhFAD3-2 module mediates drought tolerance by regulating linolenic acid biosynthesis in cotton - Yufei Liang; Luqi Wang; Yuxin Yang; Ronggui Yu; Yanping Shi; Liyong Hou; Xin Zhou; Yan Zhang; Guanghui Xiao (Science China Life Sciences, 2026)

Postbiotics alleviate cognitive impairment and neuroinflammation via gut-brain axis and TLR4/MyD88/NLRP3 pathway - Longgang Jia; Ling Xiao; Xiaoyan Song; Xiaoxiao Zhang; Xuemei Han; Wu Liang; Tianmin Fu; Yufeng Xie; Yanping Wang; Weitao Geng (Food Research International, 2025)

Complete genome sequence and molecular characterization of a novel potyvirus (sweet potato virus H) infecting sweet potato - Wei Tang; Jukui Ma; Yanping Tian; Xiao Yin; Jingwei Chen; Dongjing Yang; Fangyuan Gao; Zhao Liang; Cong Tong; Chengling Zhang; Houjun Sun (Archives of Virology, 2025)

Polysaccharides from Actinidia Lindl.: Extraction, bioactivities, and emerging applications in food and pharmaceutical industries - Lihao Wang; Chenqing Dong; Qian Wang; Chi Teng; Wuyou Gao; Yujia He; Jun Liang; Yonggang Xia; Haixue Kuang; Yanping Sun (Trends in Food Science & Technology, 2025)

Valorizing industrial and agricultural wastes into a high-performance composite for remediation of heavy metal-contaminated tailing sands - Mengjia Liang; Man Xue; Yanping Shi; Jihua Cai; Xianyu Yang; Chunzheng Jin; Zexin Chen; Maoyan Xu (Environmental Research, 2025)

MSSI: a multi-scale shift-invariant metric learning network for visible and long-wave infrared image patch matching - Xiuwei Zhang; Yanping Li; Zhaoshuai Qi; Yue Liang; Yi Sun (International Journal of Remote Sensing, 2025)

Metabolic basis of resveratrol biosynthesis in P. megaterium PH3: Key roles of phenylpropanoid precursors and enzymatic feedback inhibition - Xiaohan Zhang; Dong Zhang; Junbo Liang; Liang Wang; Yanping Cui; Dingding Feng; Shuhong Ye (Food Chemistry, 2025)

Genome-wide identification of ApeC domain-containing protein and revealing the function of ChACP-1.10 in oyster mucosal immunity - Tianxiang Lin; Lu Liu; Liang Zeng; Congxin Zhao; Shu Xiao; Haitao Ma; Jun Li; Fan Mao; Yanping Qin; Yuehuan Zhang; Yang Zhang; Zhiming Xiang; et al. (Fish & Shellfish Immunology, 2025)

Ultrasound-triggered piezocatalytic MOF(Hf)-Pt nanozymes for efficient ROS scavenging in the treatment of osteoarthritis - Yi Yao; Zixin Gao; Zhongjie Pan; Yanping Zhong; Lili Qin; Kexin Zhao; Shuhan Liu; Shengqing Zhang; Haoyang Han; Feiying Yin; Ruizheng Liang; Jinmin Zhao; et al. (Chemical Engineering Journal, 2025)

High entropy relaxation ferroelectric ceramics with strong coupled achieved by framework structure guided design and grain boundary optimisation - Renkai Zhao; Kaijie Chen; Wenhua Li; Xingui Tang; Zhifei Jian; YongXi Liang; Jiayi Yin; Yanping Jiang; Xiaobin Guo; Kai Yan (Chemical Engineering Journal, 2025)

Resveratrol inhibits autophagy in cardiomyocytes subjected anoxia/reoxygenation injury: involved in VDAC1/PINK1/Parkin pathway - Ying Zhou; Yongzhe Huang; Haiyan Liang; Xiaomei Yang; Shulin Zhang; Yinru Huang; Yanping Wan; Hangfei Zhou; An Huang; Yue Chen; Xiao Li; Yian Peng; et al. (Toxicology and Applied Pharmacology, 2025)

Comparative analysis of sheep, goat, and cow milk based on non-targeted metabolomics - Jiaxin Liu; Zhongshi Zhu; Yanping Huang; Jianping Qin; Li Wang; Mengyao Wei; Xiaorui Liu; Liang Xu; Hao Yuan; Xiaopeng An; Lei Zhang; Yuxuan Song (International Dairy Journal, 2025)

Trapping phenylacetaldehyde by litchi shell polyphenols and their characteristic catechins in chemical model and roast pork patty: Identification of catechins-adducts and toxicity assessment - Qi Chen; Yanping Xian; Ming Liang; Min Qian; Qingping Wu; Qi He; Xiaofang Zeng; Weidong Bai; Hao Dong (Food Chemistry, 2025)

Dust supply to the West Philippine Sea since the Middle Pleistocene and distinct influences of the Westerlies after the Mid-Brunhes Event - Yun Cai; Dong Xu; Haifeng Wang; Yanping Chen; Haiyan Jin; Yibing Li; Weiwei Chen; Liang Yi (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Hydrothermal reduction and phase transformation of Fe(III) minerals induced by rice straw to improve the heterogeneous Fenton degradation of metolachlor - Jingyi Liu; Yu Zhao; Liulong Cheng; Zhuoye Lu; Haojie Liang; Runliang Zhu; Yue Wang; Fangxin Deng; Zhuobiao Ni; Yaying Li; Guangwei Yu; Jing Zhang; et al. (Journal of Hazardous Materials, 2025)

The application of amendments improves properties of salt-affected soils across China - Guangzhi Huang; Baishun Liu; Xiaotong Jiang; Yanping Liang; Jinghui Cai; Lihua Huang (Soil and Tillage Research, 2025)

Biosynthetic small molecule antigens mimics medicated lateral flow immunoassay for mycotoxin Fumonisin B1 using nanobody fusion proteins - Chong Cai; Yuheng Xia; Yuanzhen Guo; Binhui Huang; Tailong Wei; Yun Liang; Qiannan Gao; Zhui Tu; Yanping Li; Qinghua He (Journal of Hazardous Materials, 2025)

Automated calibration of Noah-MP land surface model for improved irrigation representation in the North China Plain - Danqiong Dai; Yanping Li; Liang Chen; Fei Chen; Zhenhua Li; Zhe Zhang; Prasanth Valayamkunnath; Li Xu; Cenlin He; Zhuguo Ma (Journal of Hydrology, 2025)

Engineered ADSCs and doxycycline encapsulated antibacterial, immunomodulatory and proangiogenic hydrogels for infected burn wound healing - Yanan Gu; Zhen Liang; Yanping Wang; Zhou Yu; Yubo Shi; Jinlong Luo; Xianghao Xu; Ke Fang; Hanli Wang; Baolin Guo; Baoqiang Song; Xin Zhao (Chemical Engineering Journal, 2025)

Highly degradable bio-based plastic with water-assisted shaping process and exceptional mechanical properties - Jingjing Wang; Yuan Liang; Yuhan Chen; Hai Wan; Wenbin Jin; Ting Luo; Yuwei Chen; Peng Wei; Shuohan Huang; Yong He; Yanping Wang; Yumin Xia (Carbohydrate Polymers, 2025)

Recovery of Coilia nasus resources after implementation of the 10-year fishing ban in the Yangtze River: implied from the Yangtze River Estuary and its adjacent sea areas - Shuyan Wang; Ying Xiong; Hushun Zhang; Dade Song; Yanping Wang; Hui Ge; Chengbin Zhang; Long Liang; Xiaming Zhong (Frontiers in Marine Science, 2024)
Introduction The implementation of the 10-year fishing ban in the Yangtze River has provided a crucial opportunity for the recovery of rare and endangered diadromous species, such as Coilia nasus . Methods In this study, we utilized electronic length–frequency analysis (ELEFAN) and length-based Bayesian biomass estimation (LBB) method to fit the body length data of C. nasus from the Yangtze River Estuary and its adjacent sea areas before and after the fishing ban (2019-2023), and the resource changes of C. nasus population were evaluated. Additionally, combined the catch production monitoring data from 2020 to 2022, we comprehensively analyzed the impact of the Yangtze River fishing ban on the recovery of C. nasus resources. Results The results showed that: (1) The proportion of quantity, weight and occurrence frequency of C. nasus in catches showed a significant increasing trend year by year. (2) 4,994 C. nasus were caught from 2021–2023, with body lengths ranging from 13–410 mm. In 2023, the average body length and weight of C. nasus had increased by 39.93% and 133.89%, respectively, from those in 2021. (3) ELEFAN estimated that the growth parameters after fishing ban, including asymptotic length, growth coefficient, and the theoretical age at length zero, were determined to be 42.92 cm, 0.43 year -1 , and -0.31 year, respectively. The total mortality rate, fishing mortality rate, and exploitation rate were determined to be 1.47 year -1 , 0.79 year -1 , and 0.54, respectively. (4) LBB estimated that the relative fishing mortality of C. nasus before the fishing ban increased from 1.22 in 2019 to 2.65 in 2020, while the relative biomass decreased from 0.34 to 0.22. After the fishing ban, the relative fishing mortality decreased from 0.85 in 2021 to 0.06 in 2023, and the relative biomass increased from 0.26 in 2021 to 0.90 in 2023, with a significant increase in 2022, indicating a clear recovery trend in C. nasus resources. Discussion By quantifying the resource characteristics of C. nasus before and after the 10-year fishing ban on the Yangtze River, this research revealed the impact of the ban and provided a reference for future systematic evaluations of the C. nasus population.

Transcriptome analysis reveals the importance of phototransduction during the first-feeding in mandarin fish (Siniperca chuatsi) - Ke Lu; Jiaqi Wu; Shulin Tang; Di Peng; Asma Bibi; Liyun Ding; Yanping Zhang; Xu-Fang Liang (Functional & Integrative Genomics, 2024)

Sedimentary dynamics in southern Mariana Trench and its controlling factors in past 440 kyr - Zhongshan Shen; Haifeng Wang; Yanping Chen; Yun Cai; Liang Yi (Frontiers in Marine Science, 2024)
Understanding sediment dynamics and their controlling factors is essential for Quaternary studies, yet they remain poorly documented in the Mariana Trench. In this work, we examine this basic character from a sediment core collected at a depth of 6470 m from the southern part of the Mariana Trench, documenting changes in sedimentary dynamics over the past ~440 kyr. Our primary findings are as follows: (1) The median grain size is 13.6 ± 12.0 μm, and minimal changes in clay (30.9 ± 9.4%) and silt (56.6 ± 4.0%) contents, indicating a low-dynamic depositional environment; (2) Three grain-size components were identified, characterized by modal changes of ~4/60 μm, ~20 μm, and >100 μm. By comparing these results with various environmental proxies, including glacial-interglacial alternations, eolian input, and bottom-water intensity, we suggest that marine productivity has a dominant influence on deep-sea sediment dynamics, though post-depositional processes also contribute. Additionally, topographical conditions and sea-water chemistry appear to be related to the presence of coarse particles, possibly through coarse transport and micro-nodule development. Overall, grain-size parameters provide a valuable investigative tool for understanding the various influences on sediment dynamics in this region.

Evaluating AGS efficiency in PHA synthesis and extraction integrated with nutrient removal: The impact of COD concentrations - Quan Yuan; Song Chen; Yun Chen; Xinyu Zhang; Yuqing Lou; Xueting Li; Qian Liang; Yanping Zhang; Yingxue Sun (Chemosphere, 2024)

Early diagenesis, sedimentary dynamics and metal enrichment reveal deep-sea ventilation in Magellan Seamounts during the middle Pleistocene - Zhongshan Shen; Yanping Chen; Pavel Mikhailik; Yun Cai; Haifeng Wang; Liang Yi (Frontiers in Marine Science, 2024)
Seamounts are ubiquitous topographic units in the global oceans, and the Caiwei Guyot in the Magellan Seamounts of the western Pacific is a prime example. In this study, we analyzed a well-dated sediment core using magnetic properties, sediment grain size, and metal enrichment to uncover regional ventilation history during the middle Pleistocene and explore potential linkages to global climate changes. Our principal findings are as follows: (1) The median grain size is 3.3 ± 0.2 μm, and clay and silt particles exhibit minimal variation, with average values of 52.8 ± 1.8% and 38.2 ± 1.6%, respectively, indicating a low-dynamic process; (2) Three grain-size components are identified, characterized by modal patterns of ~3 μm (major one), ~40 μm, and 400–500 μm, respectively; (3) Magnetic coercivity of the deep-sea sediments can be classified into three subgroups, and their coercivity values are 6.1 ± 0.5 mT, 25.7 ± 1.0 mT, and 65.2 ± 2.1 mT. Based on these results, we propose a close linkage between magnetic coercivity and metal enrichment, correlating with changes in deep-sea circulation intensity. Conversely, sediment grain-size changes seem to be more strongly influenced by eolian inputs. Consequently, we suggest that regional ventilation has weakened since ~430 ka, likely linked to a reduction in Antarctic bottom water formation.

ChCaspase-1 cleaves ChGasdermin-E, inducing pyroptosis, and participates in the bacterial defence of the oyster Crassostrea hongkongensis - Liang Zeng; Tianxiang Lin; Lu Liu; Congxin Zhao; Ruwen Yang; Shu Xiao; Fan Mao; Yanping Qin; Haitao Ma; Yuehuan Zhang; Yang Zhang; ZiniuYu; et al. (Aquaculture, 2024)

Proton transfer induced persistent triplet charge transfer phosphorescence in molecule-doped polymer systems - Shulin Liu; Chensheng Li; Liyun Liao; Yanping Huo; Zhong-Min Su; Fu-Shun Liang; Yingxiao Mu (Chemical Engineering Journal, 2024)

Screening of promising molecules against potential drug targets in Yersinia pestis by integrative pan and subtractive genomics, docking and simulation approach - Lei Chen; Lihu Zhang; Yanping Li; Liang Qiao; Suresh Kumar (Archives of Microbiology, 2024)

Effect of long-term dosage of hydrazine on mainstream anammox process: Biofilm characteristics and microbial community - Quan Yuan; Yuqing Lou; Song Chen; Yun Chen; Xueting Li; Xinyu Zhang; Liang Qian; Yanping Zhang; Yingxue Sun (Chemosphere, 2024)

ChRIPK1 caused necroptosis signaling pathway deficiency in Crassostrea hongkongensis - Yucheng Yang; Liang Zeng; Tianxiang Lin; Lu Liu; Congxin Zhao; Shu Xiao; Haitao Ma; Jun Li; Fan Mao; Yanping Qin; Yuehuan Zhang; Yang Zhang; et al. (Fish & Shellfish Immunology, 2024)

The conversion of monolignans to sesquilignans and dilignans is closely correlated to the regulation of Arctium lappa seed germination - Rong Zhao; Ying Yu; Mingze Gao; Yanping Xing; Jianing Xue; Liang Xu; Tingguo Kang (Planta, 2024)

Quantitative evaluation and mechanism analysis of soil chemical factors affecting rice yield in saline-sodic paddy fields - Baishun Liu; Lihua Huang; Xiaotong Jiang; Ying Liu; Guangzhi Huang; Can Yang; Yanping Liang; Jinghui Cai; Ge Zhu; Qianqian Kong (Science of The Total Environment, 2024)

Electron transfer mediated photo-Fenton-like synergistic catalysis of Fe,Cu-doped MIL-101 coupled with Ag3PO4: Quantitative evaluation and DFT calculations - Xiaojuan Chen; Liang Yao; Song Xu; Juhua He; Ning Li; Jiaxin Li; Bin Liu; Yanping Zhu; Xin Chen; Hailong Wang; Runliang Zhu (Environmental Pollution, 2024)

V2O5·3H2O/N-doped graphite felt cathode efficiently produced H2O2 and ·OH in the electro-Fenton system for enhanced antibiotics degradation - Songyu Fan; Yanping Hou; Jiaxiang Liang; Tingting Zhu; Shiming Zhang; Ting Liang; Jinghui Pan; Yuxiang Shen; Zebin Yu; Hongxiang Zhu; Shuangfei Wang (Journal of Environmental Chemical Engineering, 2024)

Aquifer Water Abundance Evaluation Based on a Variable Weight Model - Aoshuang Mei; Qiang Wu; Keyao Han; Yifan Zeng; Pengfei Yang; Yanping Miao; Yang Lv; Yashuai Cui; Liang Yang (Mine Water and the Environment, 2024)

Niacin alleviates extracellular matrix deposition in ethanol + CCl4-induced liver fibrosis through the HSP90/JAK1/STAT3 axis - Yanping Fan; Meilan Xue; Tianhu Shan; Yixian Bai; Huaqi Zhang; Man Liu; Peng Wang; Xi Liang; Hui Liang (Food Bioscience, 2024)

Two-stage method recovery of metals from copper slag: Realize the resource utilization of all components - Lanbin Wang; Yangming Xu; Liang Tian; Yu Chen; Anju Yang; Guixiang Gan; Yanping Ma; Yaguang Du (Minerals Engineering, 2024)

Tungsten and oxygen dual vacancies regulation of the S-scheme ZnSe/ZnWO4 heterojunction with local polarization electric field for efficient CO2 photocatalytic reduction - Ting Liang; Zebin Yu; Yuejing Bin; Shiming Zhang; Jingwen Wei; Yujia Liu; Tingting Zhu; Songyu Fan; Yuxiang Shen; Shuangfei Wang; Yanping Hou (Chemical Engineering Journal, 2024)

A multifunctional emitter with synergistical adjustment of rigidity and flexibility for high-performance data-recording and organic light-emitting devices with “hot exciton” channel - Guowei Chen; Wen-Cheng Chen; Yaozu Su; Ruicheng Wang; Jia-Ming Jin; Hui Liang; Bingxue Tan; Dehua Hu; Shaomin Ji; Hao-Li Zhang; Yanping Huo; Yuguang Ma (Chemical Engineering Journal, 2024)

Effects of supplementary thyme on immunity responses, antioxidant indices, rumen enzymes concentrations and rumen bacteria composition in Hu sheep - Xia Du; Xindong Cheng; Kaixi Ji; Abraham Allan Degen; Yanping Liang; Xiukun Wu; Qiaoxia Dong; Mengyu Feng; Dan Jiao; Haitao Cong; Guo Yang (Animal Feed Science and Technology, 2023)

Extraction of rubidium and cesium from oilfield brine by the two-step adsorption–flotation method - Dezhen Fang; Miao Lu; Yanping Wang; Liang Ma; Kexin Li; Haining Liu; Huifang Zhang; Guosheng Shi; Zhijian Wu; Xiushen Ye (Minerals Engineering, 2023)

Hydrothermally treated peat/magnetite composites as highly efficient heterogeneous Fenton catalyst: Integrating multiple reaction mechanisms to enhance the catalytic reactivity for BPA removal - Fangxin Deng; Qingze Chen; Yanping Zhu; Xiaoliang Liang; Runliang Zhu; Yunfei Xi (Chemical Engineering Journal, 2023)

Sentinel supervised lung-on-a-chip: A new environmental toxicology platform for nanoplastic-induced lung injury - Sheng Yang; Tianyi Zhang; Yiling Ge; Yanping Cheng; Lihong Yin; Yuepu Pu; Zaozao Chen; Geyu Liang (Journal of Hazardous Materials, 2023)

Corn-straw-derived, pyridine-nitrogen-rich NCQDs modified Cu0.05Zn2.95In2S6 promoted directional electrons transfer and boosted adsorption and activation of CO2 for efficient photocatalytic reduction of CO2 to CO - Jinhang Yang; Yanping Hou; Jiangli Sun; Jingwen Wei; Shiming Zhang; Jiaxiang Liang; Zebin Yu; Hongxiang Zhu; Shuangfei Wang (Chemical Engineering Journal, 2023)

Comprehensive analysis of lncRNA-mRNA regulatory network in Populus associated with xylem development - Na Sun; Yufen Bu; Xinyuan Wu; Xiaocen Ma; Haobo Yang; Liang Du; Xiaojuan Li; Jianwei Xiao; Jinxing Lin; Yanping Jing (Journal of Plant Physiology, 2023)

Comparison of yield prediction models and estimation of the relative importance of main agronomic traits affecting rice yield formation in saline-sodic paddy fields - Baishun Liu; Ying Liu; Guangzhi Huang; Xiaotong Jiang; Yanping Liang; Can Yang; Lihua Huang (European Journal of Agronomy, 2023)

Effect of dietary Agriophyllum squarrosum on average daily gain, meat quality and muscle fatty acids in growing Tan lambs - Yanping Liang; Dan Jiao; Xia Du; Jianwei Zhou; Abraham Allan Degen; Fu Ran; Guancong Sun; Kaixi Ji; Xiukun Wu; Xindong Cheng; Xiaofei Ma; Chaoju Qian; et al. (Meat Science, 2023)

Electron-buffer-mediated dual Z-scheme ZnSe/Ag2Se/AgBr heterojunction for efficient CO2 photocatalytic reduction - Ting Liang; Jingwen Wei; Shiming Zhang; Jinhang Yang; Jiangli Sun; Zuji Li; Zhihong Li; Zebin Yu; Shuangfei Wang; Yanping Hou (Journal of Environmental Chemical Engineering, 2023)

Molecular cloning, functional characterization and expression of the β-amyrin synthase gene involved in saikosaponin biosynthesis in Bupleurum chinense DC. - Yanping Mao; Hua Chen; Jun Zhao; Yuchan Li; Liang Feng; Yuping Yang; Yiguan Zhang; Ping Wei; Dabin Hou (Journal of Plant Biochemistry and Biotechnology, 2023)

Relationships between Abyssal Redox Conditions and Rock Magnetic Properties of Surficial Sediments in the Western Pacific - Yanping Chen; Dong Xu; Huafeng Qin; Geng Liu; Yibing Li; Weiwei Chen; Liang Yi (Journal of Marine Science and Engineering, 2023)
Reconstructing changes in deep/bottom-water redox conditions are critical for understanding the role of the deep ocean in global carbon and metals cycling; nevertheless, the quantitative relationships between redox proxies and abyssal dissolved oxygen are poorly investigated. In this work, we studied the rock magnetic properties of surficial sediments in the western Pacific to investigate their relationship with regional redox conditions. Our results reveal a consistent sedimentary magnetic mineral assemblage in the western Pacific, dominated by pseudo-single-domain magnetite (Fe3O4), while the ratio of detrital and biogenic magnetite particles in different sites varies substantially. Detailed analyses identified two major magnetic-coercivity components, with modal coercivity values of 13.1 ± 1.6 mT and 54.7 ± 5.3 mT, respectively. All the magnetic parameters we measured, including both concentration-dependent and grainsize-dependent parameters, and the magnetic coercivities, are generally correlated to sedimentary redox conditions; however, the coercivities obtained by mathematical unmixing exhibit a stronger linkage, explaining about a quarter of variance of redox changes. Our findings confirm the potential of magnetic properties for tracing abyssal redox changes in the western Pacific, while the observed magnetic-redox relationships are complex and need further investigation.

Enhanced degradation of tetracycline under natural sunlight through the synergistic effect of Ag3PO4/MIL-101(Fe) photocatalysis and Fenton catalysis: Mechanism, pathway, and toxicity assessment - Xiaojuan Chen; Liang Yao; Juhua He; Jiesen Li; Song Xu; Ning Li; Yanping Zhu; Xin Chen; Runliang Zhu (Journal of Hazardous Materials, 2023)

Nitrogen doping excited Ru and Ti3C2−xNx support for hydrogen generation from ammonia borane - Licheng Liang; Linyan Bian; Yanping Fan; Shuyan Guan; Xianyun Liu; Qunying Sun; Baozhong Liu (Fuel, 2023)

Exploration of the metabolic flexibility of glycogen accumulating organisms through metatranscriptome analysis and metabolic characterization - Bin Zhao; Yanping Yang; Chen Zhao; Chunchun Zhang; Zhaohui Zhang; Liang Wang; Shang Wang; Jingfeng Wang (Journal of Environmental Sciences, 2023)

Ag3PO4-anchored La2Ti2O7 nanorod as a Z-Scheme heterostructure composite with boosted photogenerated carrier separation and enhanced photocatalytic performance under natural sunlight - Xiaojuan Chen; Jieming Chen; Ning Li; Jiesen Li; Juhua He; Song Xu; Yanping Zhu; Liang Yao; Yiqi Lai; Runliang Zhu (Environmental Pollution, 2023)

A magnetic adsorbent with metal-organic framework based on ammonium phosphomolybdenum heteropoly tungstate (AWP): Selective adsorption of Rb+ and Cs+ from aqueous resources and stripping with ammonium salts - Yanping Wang; Kexin Li; Liang Ma; Dezhen Fang; Miao Lu; Xiushen Ye; Haining Liu; Huifang Zhang; Xiaoli Tan; Zhijian Wu (Hydrometallurgy, 2023)

Preparation of recyclable and deformable POM microfiber for oil–water separation with nature-inspired top–bottom strategy - Wenbin Jin; Jingjing Wang; Hai Wan; Yuan Liang; Shuohan Huang; Yuwei Chen; Peng Wei; Qun Shao; Yanping Wang; Yong He; Yumin Xia (Chemical Engineering Journal, 2023)

Photocatalytic and oxidation mechanisms of Fe–Ag@AgCl: Effect on co-existing arsenic (III) and Escherichia coli - Yanping Cui; Qian Ye; Haili Wang; Xuewen Duo; Liang Peng; Wei Dong; Xiaoxiao Cui; Yue Lu; Yajie Li (Environmental Research, 2023)

Cu doping and Ti3C2OH quantum dots co-modifications of Zn3In2S6 boosted photocatalytic reduction of CO2 to CO via accelerating carriers transfer and enhancing CO2 adsorption and activation - Jinhang Yang; Yanping Hou; Jiangli Sun; Ting Liang; Tingting Zhu; Jiaxiang Liang; Xiaoqiong Lu; Zebin Yu; Hongxiang Zhu; Shuangfei Wang (Chemical Engineering Journal, 2023)

Impact of waste of COVID-19 protective equipment on the environment, animals and human health: a review - Sheng Yang; Yanping Cheng; Tong Liu; Shaoping Huang; Lihong Yin; Yuepu Pu; Geyu Liang (Environmental Chemistry Letters, 2022)

Early-Holocene Paleo-Tropical Cyclone Activity Inferred from a Sedimentary Sequence in South Yellow Sea, East Asia - Geng Liu; Xibin Han; Yanping Chen; Jun Li; Lehui Song; Xin Zhou; Bangqi Hu; Liang Yi (Journal of Earth Science, 2022)

Indoor air pollution from solid fuel on children pneumonia in low- and middle-income countries: a systematic review and meta-analysis - Tianming Chen; Chao Zou; Yang Yuan; Jingjing Pan; Baoping Zhang; Liang Qiao; Yanping Li; Jia-yan Qian; Qingyuan Guo; Ye Yuan; Cheng Ding (Environmental Science and Pollution Research, 2022)

The expression and interaction proteins analysis of BjuFKF1/LKP2 in B. juncea - Jing Zeng; Anran Wu; Yuemin Yang; Liang Zhao; Li Chen; Chuanqi Wang; Xin Yang; Yanping Chen; Shiyan Liu; Pei Luo; Junli Wang (Molecular Genetics and Genomics, 2022)

A novel alphahypovirus that infects the fungal plant pathogen Sclerotinia sclerotiorum - Weibo Liang; Zhongbo Lu; Jie Duan; Daohong Jiang; Jiatao Xie; Jiasen Cheng; Yanping Fu; Tao Chen; Bo Li; Xiao Yu; Weidong Chen; Yang Lin (Archives of Virology, 2022)

Magnetic minerals in Mid-Pleistocene sediments on the Caiwei Guyot, Northwest Pacific and their response to the Mid-Brunhes climate event - Liang Yi; Haifeng Wang; Geng Liu; Yanping Chen; Huiqiang Yao; Xiguang Deng (Acta Oceanologica Sinica, 2021)

Characterization of a novel brain cell line from Jian carp (Cyprinus carpio var. Jian) - Ying Li; Yanping Ma; Le Hao; Jiangyao Ma; Zhiling Liang; Zhenxing Liu; Hao Ke; Yugu Li (Fish Physiology and Biochemistry, 2021)

Contamination, distribution, and risk assessment of antibiotics in the urban surface water of the Pearl River in Guangzhou, South China - Chang Wang; Yanping Zhao; Shuang Liu; Qin Xiao; Weixin Liang; Yumei Song (Environmental Monitoring and Assessment, 2021)

The Diversity of Associated Microorganisms in Different Organs and Rhizospheric Soil of Arctium lappa L. - Yanping Xing; Yanyun Yang; Liang Xu; Ning Hao; Rong Zhao; Jiahao Wang; Shengnan Li; Dachuan Zhang; Tingting Zhang; Tingguo Kang (Current Microbiology, 2020)

Visible light-activated 1-D core-shell paramagnetic Fe-Ag@AgCl as an innovative method for photocatalytic inactivation of E. coli - Yanping Cui; Nimesha Thathsarani; Liang Peng; Ya Gao; Lidan Lei; Zhengwei Zhou; Lili Liang; Xiaoyan Shi (Environmental Science and Pollution Research, 2020)

Characterizing the effects of hypoxia on the metabolic profiles of mesenchymal stromal cells derived from three tissue sources using chemical isotope labeling liquid chromatography-mass spectrometry - Qiaoling Pan; Dan Wang; Deying Chen; Yanni Sun; Xudong Feng; Xiaowei Shi; Yanping Xu; Xian Luo; Jiong Yu; Yang Li; Hongcui Cao; Liang Li (Cell and Tissue Research, 2020)

Using 4-km WRF CONUS simulations to assess impacts of the surface coupling strength on regional climate simulation - Liang Chen; Yanping Li; Fei Chen; Michael Barlage; Zhe Zhang; Zhenhua Li (Climate Dynamics, 2019)

Determination of Fatty Acid Composition and Phospholipid Molecular Species of Large Yellow Croaker ( Pseudosciaena crocea ) Roe from China - Peng Liang; Xinwei Cheng; Yanping Xu; Wenjian Cheng; Lijiao Chen (Journal of Aquatic Food Product Technology, 2017)

Recent land cover changes and sensitivity of the model simulations to various land cover datasets for China - Liang Chen; Zhuguo Ma; Rezaul Mahmood; Tianbao Zhao; Zhenhua Li; Yanping Li (Meteorology and Atmospheric Physics, 2017)

Continental-scale convection-permitting modeling of the current and future climate of North America - Changhai Liu; Kyoko Ikeda; Roy Rasmussen; Mike Barlage; Andrew J. Newman; Andreas F. Prein; Fei Chen; Liang Chen; Martyn Clark; Aiguo Dai; Jimy Dudhia; Trude Eidhammer; et al. (Climate Dynamics, 2017)

Reproductive management through integration of PGD and MPS-based noninvasive prenatal screening/diagnosis for a family with GJB2-associated hearing impairment - WenPing Xiong; DaYong Wang; Yuan Gao; Ya Gao; HongYang Wang; Jing Guan; Lan Lan; JunHao Yan; Liang Zong; Yuan Yuan; Wei Dong; SeXin Huang; et al. (Science China Life Sciences, 2015)

Effects of Cognitive Behavioral Therapy on Insomnia of Maintenance Hemodialysis Patients - Yongmei Hou; Peicheng Hu; Yanping Liang; Zhanyu Mo (Cell Biochemistry and Biophysics, 2014)

Physical-Chemical Properties of Collagens from Skin, Scale, and Bone of Grass Carp ( Ctenopharyngodon idellus ) - Haibo Wang; Yanping Liang; Haiyin Wang; Hanjun Zhang; Min Wang; Liangzhong Liu (Journal of Aquatic Food Product Technology, 2014)

Glycosylation analysis of recombinant neutral protease I from Aspergillus oryzae expressed in Pichia pastoris - Da Lei; Yang Xu; Qinghua He; Yifeng Pan; Bo Chen; Liang Xiong; Yanping Li (Biotechnology Letters, 2013)

Transcriptional Regulation of Genes Encoding Key Enzymes of Abscisic Acid Metabolism During Melon (Cucumis melo L.) Fruit Development and Ripening - Yufei Sun; Pei Chen; Chaorui Duan; Pang Tao; Yanping Wang; Kai Ji; Yin Hu; Qian Li; Shengjie Dai; Yan Wu; Hao Luo; Liang Sun; et al. (Journal of Plant Growth Regulation, 2013)